A simple new screening tool for diagnosing imported schistosomiasis - Silvia Roure; Olga Pérez-Quílez; Xavier Vallès; Lluís Valerio; Gemma Fernández-Rivas; Belén Rivaya; Israel López-Muñoz; Laura Soldevila; Xavier Villanova; Roger Paredes; Maria-Lluïsa; Sebastián Videla; et al. (Elsevier, 2022)
Objectives: We sought to test the sensitivity and feasibility of a Schistosoma infection screening process consisting of a scored patient consultation questionnaire and a serological diagnostic test. Study design: Prospective cross-sectional study. Methods: We collected from Schistosoma-exposed individuals a 14-point check list of clinical and laboratory data related to Schistosoma infection, alongside a serological test to detect Schistosoma spp infection. A check list score was created and compared with the risk of infection and clinical recovery through an agreement analysis. Results: Two-hundred and fifty individuals were enrolled, of whom 220 (88%) were male and 30 (12%) female. The median age was 39 (range 18-78). One hundred-fifty (60%, 95% CI 54.9%-65.1%) had a check-list score ≥2. Serology test results were positive for 142 (56.8%, 95% CI 51.6%-62%). Chronic complications compatible with long-term Schistosoma infection were detected in 29 out of these 142 (20.4%, 95% CI 13.8%-27%).,. The median score value was 3, the area under the receiver operating characteristic (ROC) curve against serology results was 0.85 and the estimated intercept check-list questionnaire score value was 1.72 (95%, CI: 1.3-2.2). Participants with a positive serological test had a substantially higher check-list score (Cohen's kappa coefficient: 0.62, 95% CI: 0.54-0.70). Ninety four percent patients empirically treated showed a subsequent improvement in clinical and laboratory parameters. Conclusions: A two-component process consisting of a scored patient consultation questionnaire followed by serological assay can be a suitable strategy for screening populations at high risk of schistosomiasis infection.